Educational Robotics Competitions and Involved Methodological Aspects - Christoforou, Eftychios G.; Masouras, Panicos; Cheng, Pericles; Avgousti, Sotiris; Tsekos, Nikolaos V.; Panayides, Andreas S.; Georgiou, George K. (My University, 2019)
The present article provides perspectives on educational robotics competitions based on teaching experiences with university students as well as the organization of “Robotex Cyprus”, a widely-attended annual event. The focus is on the involved methodological aspects both from an educational and a technological/engineering viewpoint. Common approaches and good practices relevant to robot design and programming are reviewed, while selected popular competition challenges are revisited to exemplify the concepts.
Keywords: Robot competitions; Educational robotics; STEM education